2011
DOI: 10.1186/1475-2875-10-60
|View full text |Cite
|
Sign up to set email alerts
|

Pv RON2, a new Plasmodium vivax rhoptry neck antigen

Abstract: BackgroundRhoptries are specialized organelles from parasites belonging to the phylum Apicomplexa; they secrete their protein content during invasion of host target cells and are sorted into discrete subcompartments within rhoptry neck or bulb. This distribution is associated with these proteins' role in tight junction (TJ) and parasitophorous vacuole (PV) formation, respectively.MethodsPlasmodium falciparum RON2 amino acid sequence was used as bait for screening the codifying gene for the homologous protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 51 publications
0
39
1
5
Order By: Relevance
“…Each protein's main characteristics are shown. Signal sequence (dark blue), transmembrane domains (black), coiled‐coil domains (grey), and cysteine residues conserved amongst Plasmodium vivax strains (dotted red lines) (Arevalo‐Pinzon et al, ; Arevalo‐Pinzon, Curtidor, Abril, & Patarroyo, ). The locations are shown of two Pv RON2 fragments ( Pv RON2‐RI and Pv RON2‐RII) and one Pv RON4 fragment, which were cloned in vectors to be expressed in COS‐7 cells and E scherichia coli .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each protein's main characteristics are shown. Signal sequence (dark blue), transmembrane domains (black), coiled‐coil domains (grey), and cysteine residues conserved amongst Plasmodium vivax strains (dotted red lines) (Arevalo‐Pinzon et al, ; Arevalo‐Pinzon, Curtidor, Abril, & Patarroyo, ). The locations are shown of two Pv RON2 fragments ( Pv RON2‐RI and Pv RON2‐RII) and one Pv RON4 fragment, which were cloned in vectors to be expressed in COS‐7 cells and E scherichia coli .…”
Section: Resultsmentioning
confidence: 99%
“…Using P. vivax strains adapted in non‐human primates (Pico de Coana et al, ) or infected patients' blood (Bozdech et al, ) has enabled comparative approaches with other Plasmodium species (Patarroyo, Calderon, & Moreno‐Perez, ) or using omic sciences (Moreno‐Perez, Degano, Ibarrola, Muro, & Patarroyo, ; Venkatesh et al, ) to identify a significant amount of proteins expressed in P. vivax schizonts (Sch) and Mz (Patarroyo et al, ). Pv RON2 (Arevalo‐Pinzon, Curtidor, Patino, & Patarroyo, ), Pv RON4 (Arevalo‐Pinzon, Curtidor, Abril, & Patarroyo, ), and Pv RON5 (Arevalo‐Pinzon, Bermudez, Curtidor, & Patarroyo, ) have been identified recently; these are homologous to those identified in P. falciparum , which are located in the apical extreme of P. vivax Colombia Guaviare 1 (VCG‐1) strain Sch. Different biochemical techniques have been used to report a conserved Pv RON5 fragment located towards the carboxyl‐terminal extreme interacting with RBC, having a preference for CD71 + cells (Arevalo‐Pinzon et al, ), suggesting that RONs could be participating in host–parasite interactions, similar to that found in P. falciparum .…”
Section: Introductionmentioning
confidence: 83%
“…The sequence was seen to be exclusive for P. vivax and had mutations (two substitutions and four deletions), thereby suggesting that it was under pressure from the immune system. TR have been common in several P. vivax antigens described to date, which are mainly located on the surface or in apical organelles; these would include the circumsporozoite protein (CSP) [33], merozoite surface protein 9 (MSP-9) [34], Pv 34 [35] and rhoptry neck proteins 1 and 2 [23,36]. Even though several studies have shown that the tandem repeats of Pv CSP trigger an immune response when inoculated in primates and humans [33,37,38], the response so produced did not completely inhibit infection caused by the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…The anti- Pv RON4 antisera also recognized the protein on VCG-1 late-stage schizonts, having the typical apical organelle punctate pattern (Figure  3C) common to other apical proteins [8,18]. Co-localization studies using antibodies against Pv RON4 and Pv 12 showed that while Pv 12 was expressed on merozoite surface with a bunch of grapes-like pattern, Pv RON4 had a punctate pattern, not overlapping Pv 12 staining (Figure  4).…”
Section: Resultsmentioning
confidence: 99%
“…Among the various strategies being used to overcome this problem, comparative analysis with other species, such as P. falciparum and adapting P. vivax strains to Aotus monkeys [7], have allowed the identification during the last few years of several antigens in P. vivax which could be participating in invasion [8-11]. …”
Section: Introductionmentioning
confidence: 99%